The Method of Situation Analysis of International Relations as A Forecasting Tool Under Conditions of Transforming World Order - V. G. Baranovsky; I. Ya. Kobrinskaya; S. V. Utkin; B. E. Frumkin (Vestnik MGIMO-Universiteta)
The article discusses the method of situation analysis of international relations, developed in the 1960s in the Primakov National Research Institute of World Economy and International Relations by Academician Evgeniy Primakov. It has incorporated many elements of existing problem-solving methods such as “brain storm”, “Delphi”, and others. Its key innovation is understanding the international political situations under analysis as integral dynamic subsystems of international system. It proceeds in three stages: first, building a scenario of a situation development; second, getting a large number of expert assessments representing various fields of social sciences; third, producing a final document with critical summary of the assessments. Primakov encouraged organizers of situation analysis to have experts focused on the issues of practical importance, and then prepare the results of the situation analysis in a concise, understandable form to make them useful in the decisionmaking process. He viewed the method as an effective means of communicating expert knowledge to decision makers. The article reviews the method as it has been practiced in the Primakov National Research Institute of World Economy and International Relations. It gives the intellectual roots of its development, which include “grounded theory” by Barney Glaser and Anselm Strauss; systems theory by Talcott Parsons and a variant of its application to international relations by Thierry de Montbrial. The more direct roots of the method are various problem-solving techniques practiced in world’s leading international relations think-tanks such as RAND Corporation. The article also overviews the major principles of situation analysis: 1) participants must have high level of expertise; 2) situational analysis is multidisciplinary; 3) situational analysis allows focusing on key aspects of a problem when there is no clear, unambiguous understanding of it and when the views of experts vary widely; 4) to obtain significant analytical results, it is necessary to move above the situation under analysis in search of wider generalizations; 5) situational analysis is opposite to propaganda, it must be averted to conformism and partisanship; 6) situation analysis should be aimed at realizing national interests; 7) situation analysis is directed towards future. In addition to the general principles of situation analysis, the article gives two specific examples of its application. The first example is the phenomenon of the extreme-right political movements in the European Union. In this case the situation analysis gives a balanced assessment of what is happening in Russia’s neighbourhood. The second is Russia’s adoption of trade restrictive measures in response to the "sanctions" from Western countries because of the Ukrainian crisis. The situation analysis shows contradictory effects of the sanctions for the Russian economic development. These cases are small but important illustrations of global changes in both the internal life of sovereign states and the relations between them. The post-bipolar world obviously goes through a transformation, which many assess in terms of a multipolar or polycentric world order. The configuration of future polycentricity is not defined in advance and will depend on decisions of leading global players. Situation analysis can contribute to understanding and forecasting them.